Laser peripheral iridotomy in patients with acute primary angle closure - Paunović, Svetlana; Paunović, Milan; Srećković, Sunčica; Petrović, Nenad; Jovanović, Mihailo; Todorović, Dušan; Šarenac Vulović, Tatjana (Vojnosanitetski pregled, 2023)
Background/Aim. Since glaucoma has a very high prevalence worldwide, it is important to examine additional treatment modalities, especially the prevention of its progression. The aim of the study was to determine the importance of laser peripheral iridotomy (LPI) in patients with acute primary angle closure (APAC) in preventing primary angle closure glaucoma progression and APAC in the fellow eye. Methods. The research included 40 patients and 80 eyes treated between 2017 and 2021, which was also the follow-up period in the study. In all patients, LPI was performed bilaterally on both the APAC-affected eye and the healthy fellow eye. The patients with an age range from 40 to 79 years who had the pupillary block in one eye were monitored. All patients underwent bilateral LPI, and the changes in angle width were monitored using gonioscopy. Intraocular pressure (IOP) measurements were made with an applanation tonometer and Vertical Cup/Disc ratio (Ver C/D rat) performing biomicroscopic examination with indirect ophthalmoscopy and +90 D lens. Results. All 40 patients underwent bilateral LPI. The angle width of the APAC-affected eye before treatment was 0.15 ± 0.36, and 1.20 ± 0.41 of the fellow eye. After 12 months, the measurements taken were 0.85 ± 0.36 for the affected eye and 1.90 ± 0.36 for the fellow eye (Wilcoxon rank test, p < 0.01 statistically significant difference). The mean value of IOP in the eye without progression of the disease before therapy was 53.6 ± 3.73 mmHg, while in the eye with progression, it was 60.10 ± 4.37 mmHg. After 12 months, it was 14.92 ± 1.22 mmHg in the eye without progression, while in the eye with disease progression, it was 23.40 ± 2.53 mmHg (independent samples t-test, p < 0.01). The change in the Ver C/D rat in the eye without progression was 0.40 ± 0.10, while in the eye with progression, it was 0.45 ± 0.05. After 12 months, it remained unchanged in the eye without progression, while in the eye with progression, it was 0.65 ± 0.06 (independent samples t-test, p < 0.01). Conclusion. Simultaneous LPI has been proven efficient in patients with APAC in both affected and fellow eyes.
Keywords: glaucoma, angle closure; laser therapy; ophthalmologic surgical procedures